Ship Construction (6th Edition) - Hutchinson, Keith W (Elsevier, 2007)
This book is a comprehensive text for students of naval architecture, ship building and construction, and for professional naval architects and marine engineers as a refresher on the latest developments in ship types, safety and shipyard practices. Beginning with an introduction to ship building and concluding with the finished product, the book enables the reader to follow the construction of a ship from start to finish. The author explores in depth, chapter by chapter, the development of ship types, materials and strengths of ships, welding and cutting, shipyard practice, ship structure and outfitting. This new edition includes a new chapter on computer-aided design and manufacture, and all the latest international regulations and technological developments.